2015
DOI: 10.1074/jbc.m115.638932
|View full text |Cite
|
Sign up to set email alerts
|

An Ankyrin-G N-terminal Gate and Protein Kinase CK2 Dually Regulate Binding of Voltage-gated Sodium and KCNQ2/3 Potassium Channels

Abstract: Background: Neuronal axons use dense clusters of voltage-gated ion channels to conduct rapid electrical signals called action potentials. Results:We mapped sites on a cytoskeletal protein, ankyrin-G, which binds and clusters sodium and potassium channels. Conclusion: Channel binding is dually regulated by protein kinase CK2 phosphorylation and the ankyrin-G sequence. Significance: The new mechanisms identified control axonal membrane excitability and are drug development candidates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
63
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 60 publications
2
63
0
Order By: Relevance
“…In agreement with this finding, Xu and Cooper reported that the modes of Na V and KCNQ2/3 binding to ank-G differ from each other (10). Thus, our work contributes to a broadening picture of the intricate molecular arrangements that define AIS organization.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In agreement with this finding, Xu and Cooper reported that the modes of Na V and KCNQ2/3 binding to ank-G differ from each other (10). Thus, our work contributes to a broadening picture of the intricate molecular arrangements that define AIS organization.…”
Section: Discussionsupporting
confidence: 75%
“…Localization of KCNQ2/3 channels of the K V 7 family to the AIS has been proposed to follow the model of VGSCs, because KCNQ2/3 channels contain the same ank-G binding motifs that trap VGSCs (8). Moreover, VGSCs and KCNQ2/3 channels both bind to the ankyrin repeats in ank-G, albeit at distinct but overlapping interaction sites (9,10). However, other determinants for AIS localization outside of the ankyrin-binding motif have been described, thus pointing to additional modes of regulation (11)(12)(13).…”
mentioning
confidence: 99%
“…Actin rings are regularly found (at a 190-nm period) along the AIS and distal axon (17,18). Ankyrin G binds subtypes of voltage-gated sodium (Na v ) and potassium (K v ) channels via a specific analogous motif, ensuring their clustering at the AIS (19)(20)(21)(22). In mature neurons of the cortex and hippocampus, Na v 1.2 preferentially localizes to the proximal part of the AIS, while Na v 1.6 and K v 7.2/K v 7.3 cluster along the distal part (12,23,24).…”
mentioning
confidence: 99%
“…A similar binding motif is found in the distal part of the C-terminus of KCNQ2/ 3 (K V 7.2/K V 7.3). 144 Though Na V channels and K V 7.2/ K V 7.3 channels share an overlapping binding domain on Ankyrin G, the affinity of sodium channels for Ankyrin G is much stronger. The binding of both channel populations to Ankyrin G is modulated by casein kinase 2 (CK2) phosphorylation.…”
Section: Na V Channelsmentioning
confidence: 99%
“…The binding of both channel populations to Ankyrin G is modulated by casein kinase 2 (CK2) phosphorylation. 144 Blocking CK2 activity leads to a dephosphorylation of the binding motif and greater surface dynamics of Na V channels. 18 Alterations to ion channel composition and AIS size are known mechanisms of neuronal excitability tuning.…”
Section: Na V Channelsmentioning
confidence: 99%